A Model of Regenerative Architecture on a Post-Mining Land in Purwokerto - Kautsar, Alifia (ReTII, 2025)
Indonesia has a complex geological structure, offering significant potential in natural resources, particularly in the mining and excavation sectors. As an administrative city, Purwokerto has undergone rapid urban development. This growth has led to an increasing demand for construction materials, much of which is sourced from mining activities in Banyumas Regency. Such activities require land reclamation efforts to restore land productivity. Post-mining land reclamation can be carried out through several strategies, including land conversion for agricultural purposes and tourism. The conversion and recovery of land productivity are translated into the design of an Urban Farming Center as both an agricultural and edu-tourism facility within urban and suburban areas. The design process adopts a descriptive method by analyzing secondary data relevant to the planning and design of the Urban Farming Center. The data sources include spatial planning policies, site survey findings, and precedent studies of urban farming and regenerative architecture projects implemented in other regions. Primary data were obtained through site observation and analysis of existing land conditions, while secondary data were collected from scientific journals, local regulations, and urban planning documents. All data were synthesized to develop a design approach and architectural outcome. A regenerative architecture approach was applied to restore the ecosystem of the post-mining site while creating an adaptive and sustainable environment. The design of the Urban Farming Center aims not only to function as a hub for urban agriculture but also to serve as a space for education, eco-tourism, and community engagement